The faith of the Bible - Fison, J.E., (Joseph Edward), 1906-1972. (Harmondsworth, UK : Penguin, 1957)
"This book is written in the conviction that Christians and Jews have much to learn from each other and that modern man needs to rediscover the breadth and depth of ancient biblical faith". - Cover.
Includes bibliographical references and index.
Keywords: Bible -- Theology